If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6k-(7+k)=-(5k+7)
We move all terms to the left:
6k-(7+k)-(-(5k+7))=0
We add all the numbers together, and all the variables
6k-(k+7)-(-(5k+7))=0
We get rid of parentheses
6k-k-(-(5k+7))-7=0
We calculate terms in parentheses: -(-(5k+7)), so:We add all the numbers together, and all the variables
-(5k+7)
We get rid of parentheses
-5k-7
Back to the equation:
-(-5k-7)
5k-(-5k-7)-7=0
We get rid of parentheses
5k+5k+7-7=0
We add all the numbers together, and all the variables
10k=0
k=0/10
k=0
| 1/18w-1/36+1/3w=1/3+w | | X+3=2x-6=x=36 | | 4(6r+3)+2(r=2) | | (2x^2)-12x+1=-11 | | 3|-8x|8=80 | | -3/8t=7/6 | | -3x/2-5=-14 | | 10x=6+7x | | 4u+11=87 | | -7v-24=-2(v+7) | | 11/3+x=43/4 | | 6x+5=3(2x+1 | | 17=v/5+11 | | 4u+11=39 | | 1/4b+4=14 | | -79-7x=-x+95 | | 3x+8x=12 | | 11/4x=23 | | 6(3)-6x=12 | | -5y+30=50 | | -2(t-4)=10 | | 21+3x=3x+18 | | 12+.05x=10+.07x | | 5x-12=-2-5(x-2) | | f(6)=4*6-12 | | 2/3(18x-6)=-1/2(-28x+10) | | 6r–6=60r=11r=12 | | -4(-2.5x+2)=2(5x-5)+2 | | 1.5+0.1x=0.5x-5.7 | | 3x-7=8x=23 | | 6.4=8m | | 3+6x+x=24 |